Рассеяние гауссового волнового пучка на слое из метаматериала - Одаренко, Е. Н.; Свич, В. А.; Шматько, А. А. (Weber Co., 2010)
Scattering regularities of the Gaussian beam on the metamaterial slab with negative and imaginary refractive index are investigated. Theoretical analysis is carried out on the base of method of plane-wave spectral decomposition and synthesis. Regimes of the electromagnetic field propagation in the slab are considered for different system parameter values.
Keywords: метаматериал; волновой пучок; рассеяние волны